Modifications in the piperazine ring of nucleozin affect anti-influenza activity - Correa-Padilla, Erick; Hernández-Cano, Alejandro; Cuevas, Gabriel; Acevedo-Betancur, Yunuen; Esquivel-Guadarrama, Fernando; Martinez-Mayorga, Karina (PLOS ONE, 2023)
The infection caused by the influenza virus is a latent tret. The limited access to vaccines and approved drugs highlights the need for additional antiviral agents. Nucleozin and its analogs have gain attention for their promising anti-influenza activity. To contribute to the advancement of the discovery and design of nucleozin analogs, we analyzed piperazine-modified nucleozin analogs to increase conformational freedom. Also, we describe a new synthetic strategy to obtain nucleozin and its analogues, three molecules were synthesized and two of them were biologically evaluated in vitro. Although the analogues were less active than nucleozin, the loss of activity highlights the need for the piperazine ring to maintain the activity of nucleozin analogs. Interestingly, this result agrees with the prediction of anti-influenza activity made with a QSAR model presented in this work. The proposed model and the synthetic route will be useful for the further development of nucleozin analogs with antiviral activity.